Pengaruh Pendapatan dan Gaya Hidup terhadap Pola Konsumsi Masyarakat Kelurahan Padang Tangah Payobadar Kecamatan Payakumbuh Timur Kota Payakumbuh - Agustria, Fadilah; Martilova, Novera (AHKAM, 2025)
The problem examined in this research is the influence of income and lifestyle on the consumption patterns of the people of Pandang Tangah sub-district, East Payakumbuh sub-district, Payakumbuh city. This research aims to find out and analyze how much influence income and lifestyle have on the consumption patterns of the people of Padang Tangah Payobadar sub-district, East Payakumbuh sub-district, Payakumbuh city. This research uses a quantitative approach with quantitative descriptive methods. The researchers used data collection techniques through surveys, observations and questionnaires. The data used in this research is primary data. The analysis techniques used are research instrument tests (validity and reliability tests), classical assumption tests (normality test, multicollinearity test, heteroscedasticity test, autocorrelation test), multiple linear regression test, determinant coefficient test, hypothesis test (T test and F test) . so that it can be seen the influence of income and lifestyle on the consumption patterns of the people of Padang Tangah Payobadar sub-district, East Payakumbuh sub-district, Payakumbuh city. The results of the research show that the income variable has a t-count > t-table value (3.997 > 1.985) with a significant value of 0.001 < 0.05, which means that the income variable has a significant and influential effect on the consumption patterns of the people of Padang Tangah Payobadar sub-district, East Payakumbuh sub-district, Payakumbuh city. The lifestyle variable has a value of t-count < t-table (0.720 < 1.985) with a significance of 0.473 > 0.05) which means that the lifestyle variable has no effect on the consumption patterns of the people of Padang Tangah Payobadar sub-district, East Payakumbuh sub-district, Payakumbuh city. Simultaneously, income and lifestyle on the consumption patterns of the people of Padang Tangah Payobadar sub-district, East Payakumbuh sub-district, Payakumbuh city has a value of f-count > f-table (16.384 > 3.09) with a significant value of (0.001 < 0.05) which means lower income and Lifestyle simultaneously influences the consumption patterns of the people of Padang Tangah Payobadar sub-district, East Payakumbuh sub-district, Payakumbuh city.